Study protocol of the Center for Oral Health Research in Appalachia (COHRA) etiology study - McNeil Daniel W; Crout Richard J; Weyant Robert J; Polk Deborah E; Tarter Ralph E; Thomas John G; Marazita Mary L (BMC, 2008)
Abstract Background People in Appalachia experience some of the worst oral health in the United States. To develop effective intervention and prevention strategies in Appalachia, we must understand the complex relationships among the contributing factors and how they affect the etiology of oral diseases. To date, no such comprehensive analysis has been conducted. This report summarizes the characteristics of the sample and describes the protocol of a study determining contributions of individual, family, and community factors to oral diseases in Appalachian children and their relatives. Methods/Design Families participated in a comprehensive assessment protocol involving interviews, questionnaires, a clinical oral health assessment, a microbiological assessment, and collection of DNA. The design of the study is cross-sectional. Conclusion Due to its multilevel design and large, family-based sample, this study has the potential to greatly advance our understanding of factors that contribute to oral health in Appalachian children.